(untitled) (ENTHYMEMA, 2010)
The rapid growth of the neurosciences has generated a widespread interest for their results also in the fields of philosophy and aesthetics. Yet, to avoid both a superficial syncretism and an aprioristic rejection, we have to consider the theoretical and methodological issues that necessarily come up when we use neuroscientific categories and methods in researches whose object is literature. The article tries to give a contribution to this end. Through the observation of some neuroscientific researches and building on the observations of the neuroscientists themselves, the author analyzes the problem of the correlation between different categories and he proposes a position which stands between Donald Davidson’s anomalous monism and nomological monism. Finally, he defines some hypotheses regarding the contribution that we can expect from the neurosciences for those sciences and disciplines that are centred on our experience or our psyche. In the second part, as an experiment to assess the fertility of the conclusions and hypotheses that are reached here, Vittori Alfieri’s Vita will be read on their ground.